Healthcare Costs for Older Patients Before and After Inpatient Rehabilitation: A Retrospective and Prospective Longitudinal Cohort Study - Bachmann, Stefan; Pfaundler, Nubio; Oesch, Peter; Kool, Jan Pieter (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Background Little is known about the costs incurred over the 12 months before and after inpatient geriatric rehabilitation in Switzerland.Objectives To compare direct healthcare costs for elderly patients over a period of 12 months before and after inpatient rehabilitation and to determine predictive factors for costs after discharge.Design Retrospective and prospective cohort study.Patients and Methods Elderly patients referred for inpatient rehabilitation to the rehabilitation centre Walenstadtberg of Kliniken Valens, Switzerland, were included. Cost data were collected from healthcare insurance providers. Comparisons of costs before and after discharge from rehabilitation were performed. The effect of patient characteristics (Multimorbidity, Health-related quality of life, Age, Vulnerability, Independence in activities of daily living, Sex, and Mobility) on costs 12 months before and after rehabilitation was evaluated with regression analysis.Results A total of 210 patients were enrolled, and 136 completed the clinical follow-up. Seventy-five patients were included in the cost analysis. Total mean healthcare costs per person in the 12-month period before discharge were CHF 24 429, compared with CHF 18 154 in the 12-month period after discharge. After rehabilitation lower costs were reported for hospital admissions, while costs for drugs and therapy were significantly higher. Multimorbidity and health-related quality of life were predictors of costs before rehabilitation (adjusted R-square 0.183). Higher costs after rehabilitation were predicted by higher multimorbidity (adjusted R-square 0.09), lower independence in activities of daily living (adjusted R-square 0.04) and lower health-related quality of life (adjusted R-square 0.03).Conclusion The mean total costs before geriatric rehabilitation were significantly higher compared with the mean costs after discharge from geriatric rehabilitation. In particular, the mean costs for hospitalizations were lower after rehabilitation. Multimorbidity and lower health-related quality of life predicted higher costs before and after rehabilitation.
Keywords: Costs; Elderly; Rehabilitation; Economics; Hospitalization